A set of refactorings for the evolution of Fortran programs. (2016) - Rissetti, Gustavo; Charão, Andrea Schwertner; Piveta, Eduardo Kessler
The formula translation (Fortran) language, despite having almost 60 years of existence, is still widely used in scientific applications. The majority of Fortran applications still in use is composed of legacy code, sometimes using obsolete or deprecated language features and, thus, thriving for updates to improve their quality attributes though evolution. Software evolution can be benefited from refactoring which provides well-defined mechanisms to be followed, helping to maintain and to improve the quality of existent systems. We present a set of refactorings for the evolution of Fortran programs and automate a set of them in the Photran framework.